Eco-HR : integrating sustainability into workforce management - Kaur, Jaspreet (Emerald Publishing Limited, 2026)
Eco-HR: Integrating Sustainability into Workforce Management explores the critical intersection of environmental sustainability and human resource management. A diverse team of authors provides HR professionals with actionable solutions, practical examples, and proven strategies to embed sustainability into the workplace. By empowering organisations to adopt eco-friendly practices, it aims to drive meaningful change while addressing the growing demand for sustainable operations. Blending theory with practice, this contributed work delves into how sustainability can be seamlessly integrated into core HR functions such as staffing, employee development, morale enhancement, and cultural transformation. Featuring best practices, step-by-step guidelines, and real-world examples, it equips HR managers, sustainability officers, academics and organisational leaders with the tools to foster an environmentally responsible workforce. Whether you're seeking to implement green policies or transform your organisational culture, this resource offers the insights and guidance to make sustainability a tangible reality.